Ecosystem structural changes controlled by altered rainfall climatology in tropical savannas - Wenmin Zhang (Nature Portfolio, 2019)
Changing rainfall patterns may drive changes in the structure of tropical savanna. Here Zhang et al. use satellite data from global tropical savannas, and find evidence to suggest that altered rainfall may be favouring woody plants over herbaceous plants in these ecosystems.